2021
DOI: 10.3390/cancers13215440
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Proteomic Analysis Dissects the Complexity of Tumor Microenvironment in Muscle Invasive Bladder Cancer

Abstract: Muscle invasive bladder cancer (MIBC) is a malignancy with considerable heterogeneity. The MIBC tumor microenvironment (TME) is highly complex, comprising diverse phenotypes and spatial architectures. The complexity of the MIBC TME must be characterized to provide potential targets for precision therapy. Herein, an integrated combination of mass cytometry and imaging mass cytometry was used to analyze tumor cells, immune cells, and TME spatial characteristics of 44 MIBC patients. We detected tumor and immune c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…The data table integrates single ion signals per pixel, after which image and single cell segmentation can be converted to single-cell data for downstream analysis. In cancer research, IMC is used to discover novel phenotypes and biomarkers, or to study TME heterogeneity [22][23][24][25][30][31][32]36,43,44,50]. IMC is also used to predict prognosis and therapy responses in humans or in mice [23,30,51,[65][66][67][68][73][74][75].…”
Section: Imaging Mass Cytometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The data table integrates single ion signals per pixel, after which image and single cell segmentation can be converted to single-cell data for downstream analysis. In cancer research, IMC is used to discover novel phenotypes and biomarkers, or to study TME heterogeneity [22][23][24][25][30][31][32]36,43,44,50]. IMC is also used to predict prognosis and therapy responses in humans or in mice [23,30,51,[65][66][67][68][73][74][75].…”
Section: Imaging Mass Cytometrymentioning
confidence: 99%
“…In cancer research, IMC is used to discover novel phenotypes and biomarkers, or to study TME heterogeneity [22][23][24][25][30][31][32]36,43,44,50]. IMC is also used to predict prognosis and therapy responses in humans or in mice [23,30,51,[65][66][67][68][73][74][75].…”
Section: Imaging Mass Cytometrymentioning
confidence: 99%
“…Bladder tumors and normal adjacent tissue, young and aged murine bladders scRNA-seq, scTCR-seq, sc-CyTOF (Chen et al, 2020;Ligon et al, 2020;Oh et al, 2020;Wang et al, 2021b;Feng et al, 2021) The detection of urinary exfoliated tumor cells…”
Section: Human Mousementioning
confidence: 99%
“…For example, Kubli, SP et al proposed that the complexity of immune cell-cancer cell interaction is an important reason for the failure of tumor immunotherapy [ 67 ]. Besides, Feng, C et al, Prokhnevska, N et al and Wierz, M et al described the complexity of the tumor microenvironment in bladder cancer, prostate cancer, and chronic lymphocytic leukemia, respectively [ 68 70 ]. Taken together, we believe that the results of the immune infiltration analysis not only showed that the main immune cells exhibited a higher degree of immune infiltration in the low-risk group, but also provide some clues about the complexity of immune cell roles in HNSCC.…”
Section: Discussionmentioning
confidence: 99%